Extraction Optimization of Phenolics from Beta Vulgaris Stems by High-Intensity Ultrasound with Response Surface Methodology Approach - Muñoz-Reaño, Pedro Isaac; Villagrán, Zuamí; Aurora-Vigo, Edward F.; Rodríguez-Laffite, Ernesto; Silva-Jara, Jorge Manuel; Montalvo-González, Efigenia; Schmiele, Marcio; Anaya-Esparza, Luis Miguel (Trends in Sciences, 2025)
High-intensity ultrasound-assisted extraction was used to extract total soluble phenols, flavonoids, and anthocyanins from Beta vulgaris stems, and to evaluate their antioxidant activities (DPPH, ABTS, and FRAP). The effect of extraction time (X1: 2, 4, and 6 min), ultrasound power (X2: 80%, 90% and 100%), and liquid-to-solid ratio (X3: 10:1, 15:1, and 20:1 mL/g) was investigated using response surface methodology. The high-intensity ultrasound-assisted extraction models for all responses were adjusted to a 2nd-order polynomial equation (R2 = 0.94 - 0.99, lack of fit > 0.05). Optimal high-intensity ultrasound-assisted extraction conditions differ for each response, X1: 3.08 min, X2: 100%, and X3: 17.32:1 mL/g for total soluble phenols, X1: 5.99 min, X2: 95.04% and X3: 17.28:1 mL/g for total flavonoids, and X1: 6 min, X2: 92.24%, and X3: 12.97:1 mL/g for total anthocyanins. Moreover, all evaluated conditions exhibited antioxidant properties by DPPH, ABTS, and FRAP. Furthermore, the validated high-intensity ultrasound-assisted extraction conditions (3.08 min for extraction time, 100% power ultrasound, and 17.32 mL/g of liquid-to-solid ratio) yielded 2.35 times higher soluble phenols content than conventional extraction method (magnetic stirring at 400 rpm for 60 min), with higher (p ˂ 0.05) flavonoids, ABTS, and FRAP values, and similar values (p > 0.05) for anthocyanins and DPPH. Furthermore, shikimic, protocatechuic, 4-hydroxybenzoic, gallic, chlorogenic, neochlorogenic, and trans-ferulic acids were higher under high-intensity ultrasound-assisted extraction than conventional extraction according to the HPLC analysis. It demonstrated that high-intensity ultrasound-assisted extraction is an efficacious technology for extracting bioactive molecules. In addition, future research could focus on isolating and purifying the phenolic compounds extracted from B. vulgaris stem powder, which have potential applications in food and non-food industries. HIGHLIGHTS Beta vulgaris stems are a source of phytochemicals Ultrasound is a viable technology for extracting bioactive compounds Beta vulgaris extracts exhibited antioxidant properties GRAPHICAL ABSTRACT